PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP PRESTASI BELAJAR MATEMATIKA ARITMATIKA SOSIAL SISWA KELAS VII SMP NEGERI 3 KOTA PALU - Marina Marina; Indah Suciati (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study aims to find out whether the contextual learning approach is effectively applied to the learning process in the classroom seen from student achievement. The type of research used is quantitative experiment research with quasi-experimental research methods. The population of this study were all class VII SMP Negeri 3 Palu registered in 2018/2019 as many as 339 students. the sampling technique is purposive sampling which in sampling the researcher has certain considerations in taking the sample, in this study the researcher requires two classes that are homogeneous in their abilities and can represent the characteristics of the population. The results of learning achievement using a contextual approach obtained an average value of 84.5 while the class using the conventional method obtained an average value of 69.5. Based on the results of the calculation of paired sample test analysis, the t value was -46.934 with a significance of 0.000 <0.05 where there were differences in mathematics learning achievement of students taught using a contextual approach with students taught using conventional methods that were quite significant, with in other words there is the influence of the contextual approach to the achievement of students' social arithmetic mathematics learning